2007
DOI: 10.1016/j.exer.2007.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of outer retina and its synaptic connectivity following subretinal injections of human RPE cells in the Royal College of Surgeons rat

Abstract: We have examined how transplantation of an RPE cell line to the subretinal space of RCS rats affects the distribution of synaptic connectivity markers in the outer plexiform layer of the retina. Using markers of pre-and post-synaptic profiles (bassoon and synaptophysin as presynaptic markers and mGluR6 for postsynaptic profiles) we found that the normal orderly patterns seen between photoreceptors and rod and ON-cone bipolar cells were severely disrupted in dystrophic rats. In areas in which injected cells pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
42
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 36 publications
3
42
0
Order By: Relevance
“…In this study, we have shown that photoreceptors were absent in control retinas but were maintained in retinas transplanted with rat and human IPE cells, as well as in rats transplanted with human RPE cells as has been shown previously [15,18,19,40,41,49]. The findings of this study suggest that IPE cells possess neurotrophic characteristics that make them a promising candidate cell for transplantation to treat retinal degenerations, especially if these cells are genetically modified to express specific factors that correct genetic deficiencies of a specific function.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In this study, we have shown that photoreceptors were absent in control retinas but were maintained in retinas transplanted with rat and human IPE cells, as well as in rats transplanted with human RPE cells as has been shown previously [15,18,19,40,41,49]. The findings of this study suggest that IPE cells possess neurotrophic characteristics that make them a promising candidate cell for transplantation to treat retinal degenerations, especially if these cells are genetically modified to express specific factors that correct genetic deficiencies of a specific function.…”
Section: Discussionsupporting
confidence: 59%
“…Several research groups are evaluating various genetically modified cell lines or stem cells, with the ultimate goal of transplanting them into the subretinal space. In practice, these cells, such as Schwann cells [12][13][14][15], bone marrow stem cell [16], prenatal human brain progenitors [17] as well as cell lines [18][19][20][21] are evaluated for effectiveness by analyzing their effect on the rescue of photoreceptors in the RCS rat.…”
Section: Introductionmentioning
confidence: 99%
“…This improvement was mostly achieved by adding a small permanent magnet in an off-axis configuration to the MM-OCT setup. The thickness of the permanent magnet is only 2 mm; hence, the reduction of working distance from 6 mm (relative to the surface of the solenoid) in the original setup to 4 mm (relative to the surface of In a final step, we tested our rMM-OCT imaging method on alternative cells next to MSCs that are used for retinal transplantation studies concerning the RPE, the ARPE-19 cell line [13][14][15]. These cells were labeled and embedded in agar scaffolds identical to MSCs, as described before.…”
Section: Discussionmentioning
confidence: 99%
“…However, rMM-OCT provides a significantly improved magnetomotive contrast compared to MM-OCT, although the charging voltage was four times smaller and, thus, the solenoid's power consumption was 16 times lower. In a final step, we tested our rMM-OCT imaging method on alternative cells next to MSCs that are used for retinal transplantation studies concerning the RPE, the ARPE-19 cell line [13][14][15]. These cells were labeled and embedded in agar scaffolds identical to MSCs, as described before.…”
Section: Cell Imagingmentioning
confidence: 99%
“…Other approaches for advanced retinal degeneration which remain experimental at the present time include retinal pigment epithelial (RPE) transplantation [10,63,64,85,104] and photoreceptor (PR) transplantation [7,14,37,65,109]. Gene therapy is extremely promising; however, its potential in advanced retinal dystrophy is currently unknown [1,8,15,47,77,83,110,111,115,118,123].…”
Section: Introductionmentioning
confidence: 99%